2007
DOI: 10.1080/02656730601150522
|View full text |Cite
|
Sign up to set email alerts
|

A head and neck hyperthermia applicator: Theoretical antenna array design

Abstract: Purpose: Investigation into the feasibility of a circular array of dipole antennas to deposit RF-energy centrally in the neck as a function of: 1) patient positioning, 2) antenna ring radius, 3) number of antenna rings, 4) number of antennas per ring and 5) distance between antenna rings. Materials and Methods: Power absorption (PA) distributions in realistic, head and neck, anatomy models are calculated at 433MHz. Relative PA distributions corresponding to different set-ups were analysed using the ratio of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 22 publications
3
38
0
Order By: Relevance
“…3. Picture of the measurement setup with 12 antennas at staggered locations in two rings [20]. Also visible are 1) the centrally placed bottle containing saline water, 2) the gauze that forms the conducting backplane (limitedly visible) and separate conducting backplanes per antenna, and 3) the flat muscle phantom on which the antenna ring is positioned.…”
Section: Clinical Antenna Setup: Measurements and Simulationmentioning
confidence: 99%
See 2 more Smart Citations
“…3. Picture of the measurement setup with 12 antennas at staggered locations in two rings [20]. Also visible are 1) the centrally placed bottle containing saline water, 2) the gauze that forms the conducting backplane (limitedly visible) and separate conducting backplanes per antenna, and 3) the flat muscle phantom on which the antenna ring is positioned.…”
Section: Clinical Antenna Setup: Measurements and Simulationmentioning
confidence: 99%
“…In previous publications [2], [20] we have shown that the optimum setup for an H&N hyperthermia applicator is a circular array (diameter 40 cm) of two rings of six antennas (spacing between rings 6 cm). We constructed such a setup to measure the reflection characteristics of the patch antenna design within the applicator, and as such validate our theoretical analysis.…”
Section: Clinical Antenna Setup: Measurements and Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…The platform has also been used to develop a novel head and neck applicator [10,11] and to assess the safety of hyperthermia in the presence of metallic implants. It was validated on the basis of dosimetric measurements and clinical information.…”
Section: Rsfsroyalsocietypublishingorg Interface Focus 3: 20120058mentioning
confidence: 99%
“…Penetration deeper in tissue using a phased array of microwave antennas has been proposed (Arcangeli et al, 1984, Gross et al, 1990) and prototype arrays designed specifically for neck tumors are currently under development (Paulides et al, 2007b, Paulides et al, 2010, Togni et al, 2013. Radiofrequency phased-array systems are also available that can penetrate deep in the body, but the long wavelength generates a large heat focus (Canters et al, 2009, Van Rhoon et al, 2003, Fatehi and van Rhoon, 2008.…”
Section: Introductionmentioning
confidence: 99%